Composite high-performance water-absorbent resin material and preparation process thereof

By combining natural polysaccharides with synthetic monomers and modifying them, combined with the use of multi-sensor monitoring systems, the shortcomings in environmental friendliness, cost and mechanical properties of water-absorbing resin materials are solved, and a significant improvement in water-absorbing, expansion and mechanical properties are achieved.

CN119684520APending Publication Date: 2025-03-25SHANDONG LUQIANG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411873352.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing water-absorbing resin materials have shortcomings in environmental friendliness, raw material costs and mechanical properties, resulting in challenges in the context of increased environmental protection and sustainability requirements.

Method used

By combining natural polysaccharides with synthetic monomers, adding crosslinking agents and initiators, and modifying methods such as graft copolymerization, sulfonation and aminolation, the preparation process is optimized and the use of a multi-sensor monitoring system is used to finely control the crosslinking reaction conditions.

Benefits of technology

It significantly improves the water absorption, expansion, mechanical properties and biodegradability of water-absorbing resin materials, solves the problems of environmental friendliness, cost and mechanical properties, and improves the comprehensive performance and production stability of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684520A_ABST
    Figure CN119684520A_ABST
Patent Text Reader

Abstract

The invention relates to the field of high polymer materials, and discloses a composite high-performance water-absorbent resin material which comprises the following components in percentage by weight: 5-10% of natural polysaccharide, 16-55% of synthetic monomer, 3-10% of cross-linking agent and 0.1-2% of initiator. By adopting the technical scheme of compounding the natural polysaccharide and the synthetic monomer, the natural polysaccharide is structurally modified through modification methods such as graft copolymerization, sulfonation and amination, and the cross-linking property and hydrophilicity of the natural polysaccharide are remarkably enhanced. The modified natural polysaccharide is compounded with an acrylic monomer, and a cross-linking agent and an initiator are supplemented, so that the composite water-absorbent resin material with excellent water absorption, expansibility and mechanical strength is formed. The introduction of the natural polysaccharide not only improves the environmental protection property, biocompatibility and degradability of the material, but also solves the problems of poor water absorption, poor expansibility and insufficient mechanical strength of the natural polysaccharide by the application of the modification method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a composite high-performance water-absorbing resin material and a preparation process thereof. Background Art

[0002] Water-absorbent resins, especially high-performance water-absorbent resins, are widely used in sanitary products (such as diapers, sanitary napkins), agricultural irrigation, soil improvement, and environmental protection fields (such as wastewater treatment). These water-absorbent resins are usually polymer materials made by chemical synthesis and have excellent water absorption and swelling properties. However, with the continuous improvement of environmental protection and sustainability requirements, the problems of traditional water-absorbent resin materials in biodegradability, environmental friendliness, and cost control have gradually emerged, and it is urgent to innovate and optimize their production process and material composition.

[0003] Composition and properties of water-absorbent resins in the prior art

[0004] In the prior art, water-absorbent resin materials are mostly cross-linked from synthetic polymer monomers (such as acrylic monomers) using initiators such as ammonium persulfate for free radical polymerization. Although the synthesis method can obtain resins with certain water absorption and expansion properties, it still has the following shortcomings:

[0005] Poor environmental friendliness: Most existing water-absorbent resin materials rely on petrochemical-based materials, such as acrylic acid and its derivatives, which causes great pressure on the environment during their production process and post-waste treatment. In particular, the non-degradability of such water-absorbent resin materials causes long-term environmental pollution during waste disposal and degradation after use.

[0006] High cost of raw materials: Most of the water-absorbent resin materials currently in widespread use are based on petrochemicals. The monomer synthesis process is complex and costly, which makes it difficult to effectively reduce the cost of the final product and limits its application in some low-cost products.

[0007] Insufficient mechanical properties: Most water-absorbent resins in the prior art are produced through simple cross-linking reactions, and lack precise control of reaction conditions during the cross-linking process. Therefore, in the process of improving water absorption and swelling, problems such as unstable mechanical properties and large fluctuations in water absorption often occur. This limits the application of these materials in certain high-requirement fields (such as high-strength water-absorbent materials).

[0008] Therefore, the present invention proposes a composite high-performance water-absorbing resin material and a preparation process thereof to solve the deficiencies of the prior art. Summary of the invention

[0009] The present invention provides a composite high-performance water-absorbing resin material and a preparation process thereof, aiming to solve the deficiencies of the water-absorbing resin material in the prior art in terms of environmental friendliness, raw material cost, mechanical properties, etc.

[0010] To achieve the above objectives, the present invention is implemented by the following technical scheme: a composite high-performance water-absorbing resin material, which is composed of a natural polysaccharide and a synthetic monomer, and contains a cross-linking agent and an initiator. The formula of the composite material is as follows:

[0011] Natural polysaccharides: 5%-10%wt

[0012] Natural polysaccharide is one of the key components of the present invention. Natural polysaccharide (carboxymethyl cellulose, chitosan, xylan, sodium alginate or a combination thereof) has excellent biocompatibility, environmental protection and good degradability. Through compounding with synthetic monomers, natural polysaccharide can effectively enhance the water absorption, swelling and biodegradability of water-absorbing resin, while reducing the environmental burden of the material.

[0013] Synthetic monomer: 16%-55%wt

[0014] Synthetic monomers are usually polymer monomers such as sodium acrylate, acrylic acid, and vinyl ether. Sodium acrylate and acrylic acid have excellent hydrophilicity, which helps the water absorption and expansion of the water-absorbing resin. Vinyl ether enhances its mechanical properties and structural stability by adjusting the cross-linking density and stability of the resin. The reasonable ratio of synthetic monomers ensures the excellent performance of the resin material.

[0015] Crosslinking agent: 3%-10%wt

[0016] Crosslinking agents (such as N,N'-methylenebisacrylamide) play a vital role in the preparation of water-absorbent resins. They can form a three-dimensional network structure during the polymerization process, making the resin have high strength, stability and water absorption capacity. The addition of crosslinking agents can significantly improve the compressive and tensile properties of resin materials, and enhance their reliability and durability in practical applications.

[0017] Initiator: 0.1%-2%wt

[0018] Initiators (such as ammonium persulfate or hydrogen peroxide) are used to start free radical polymerization reactions and promote the polymerization of synthetic monomers. The selection and concentration adjustment of initiators have an important influence on the reaction start-up speed, polymerization rate, and the structure and properties of the final resin. Reasonable control of the amount of initiator used can ensure the high efficiency of the polymerization reaction and avoid side reactions.

[0019] Preferably, the natural polysaccharide is carboxymethyl cellulose, chitosan, xylan, sodium alginate or a combination thereof, and the molecular weight of the natural polysaccharide is 10,000-1,000,000 Da, and the natural polysaccharide is structurally modified by graft copolymerization, sulfonation, and amination to enhance its cross-linking reactivity with synthetic monomers.

[0020] Graft copolymerization is a common structural modification method. It involves polymerizing natural polysaccharides with certain synthetic monomers so that the synthetic monomers are grafted onto the molecular chains of natural polysaccharides, thereby enhancing the functionality and cross-linking properties of natural polysaccharides.

[0021] step:

[0022] Selection of natural polysaccharides: Select natural polysaccharides suitable for graft copolymerization, such as carboxymethyl cellulose, chitosan, xylan, sodium alginate, etc. Usually, the molecular weight of natural polysaccharides should be controlled between 10,000-1,000,000Da to ensure good solubility and cross-linking properties.

[0023] Dissolving natural polysaccharides: dissolving natural polysaccharides in a suitable solvent (such as water or an organic solvent) to make a solution of a certain concentration (such as 5%-10% wt) so as to react with the synthetic monomers.

[0024] Selection of synthetic monomers: Select synthetic monomers with strong reactivity, such as acrylic acid, sodium acrylate, vinyl ether, etc., as grafting comonomers.

[0025] Adding initiator: Adding initiator (such as ammonium persulfate, hydrogen peroxide, etc.) to the natural polysaccharide solution to start the free radical polymerization reaction. The commonly used initiator is ammonium persulfate, with a concentration of 0.1%-2%wt.

[0026] Graft copolymerization reaction: The reaction is carried out at an appropriate temperature (generally 40°C-70°C) and pH value (usually 4.5-7). The reaction time can be controlled within 1-5 hours to ensure that the grafting reaction is sufficient. The graft copolymerization effect can be optimized by adjusting the temperature, pH, reaction time and other conditions.

[0027] Termination reaction: After the reaction is completed, the polymerization reaction is terminated by adding a terminator (such as sodium bisulfite) to end the reaction process.

[0028] Post-treatment: The grafted natural polysaccharide is treated, such as washing with water, drying, etc., to remove unreacted monomers and impurities to obtain the modified natural polysaccharide after graft copolymerization.

[0029] Advantages: Through graft copolymerization, synthetic monomers can be introduced into the molecular chain of natural polysaccharides, significantly improving their cross-linking properties with other monomers and enhancing the water absorption, expansion and mechanical strength of the composite resin.

[0030] Sulfonation modification method

[0031] Sulfonation refers to the introduction of certain functional groups (such as hydroxyl groups) of natural polysaccharides into sulfonic acid groups through sulfuric acid or sulfate chemical reactions, thereby changing their hydrophilicity and charge properties and improving their reactivity with synthetic monomers.

[0032] step:

[0033] Choose natural polysaccharides: Choose natural polysaccharides, such as chitosan, xylan, sodium alginate, etc., and ensure that they have sulfonated functional groups.

[0034] Dissolving natural polysaccharides: Dissolve the natural polysaccharides in a suitable solvent, such as deionized water or a dilute acid solution, to form a 5%-10% wt solution.

[0035] Sulfonation reaction: Slowly add the sulfonation reagent (such as concentrated sulfuric acid, sodium bisulfite or sulfonate esterification reagent) to the natural polysaccharide solution. The reaction temperature is generally controlled between 0°C and 30°C to avoid high temperature causing degradation of the natural polysaccharide.

[0036] Reaction time: The reaction time is 1-4 hours. The amount of sulfonic acid groups introduced can be adjusted by controlling the concentration of the sulfonating agent and the reaction time.

[0037] Termination of reaction: After the reaction is completed, add excess water or dilute sulfuric acid to neutralize the excess sulfonating agent to terminate the sulfonation reaction.

[0038] Post-treatment: remove impurities by water washing and then dry to obtain sulfonated modified natural polysaccharide.

[0039] Advantages: Sulfonated natural polysaccharides have higher hydrophilicity and charge density, which helps to improve the compatibility with synthetic monomers and enhance the water absorption, expansion and mechanical strength of the composite resin.

[0040] Amination modification method

[0041] Amination refers to the introduction of amino groups (-NH2) into the molecular chains of natural polysaccharides to make them more hydrophilic and reactive with other chemical substances (such as cross-linking agents, synthetic monomers, etc.).

[0042] step:

[0043] Select natural polysaccharides: Select natural polysaccharides such as chitosan and carboxymethyl cellulose as raw materials for amino modification.

[0044] Dissolving natural polysaccharides: Dissolve natural polysaccharides in deionized water or a suitable solvent to form a 5%-10% wt solution.

[0045] Adding an amination agent: Add an amination agent (such as ammonia gas, ammonia water or an aminosilylating agent) to carry out an amination reaction. The reaction temperature is usually controlled between 40°C and 60°C, and the reaction time is 2-4 hours.

[0046] Reaction process: amino groups are introduced into the molecular chain of natural polysaccharides through amination reaction. During the reaction, the degree of amination can be adjusted by controlling the concentration of the amination agent and the reaction time.

[0047] Termination of the reaction: After the reaction is completed, the unreacted reagent is removed by washing with water, and the amino-modified natural polysaccharide is obtained by drying.

[0048] Advantages: The amino groups of the aminated natural polysaccharides are increased, which significantly improves their reactivity with cross-linking agents and synthetic monomers, further enhancing the water absorption and expansion of the composite resin.

[0049] Through graft copolymerization, sulfonation and amination modification methods, the cross-linking, hydrophilicity and material performance of natural polysaccharides and synthetic monomers can be effectively improved. In the preparation of composite high-performance water-absorbent resin materials, these modification methods can significantly improve the water absorption, expansion, mechanical strength and environmental adaptability of the materials, thereby solving the performance problems existing in the existing technology, and have strong innovation and application potential.

[0050] These natural polysaccharides are selected as raw materials mainly based on their following advantages:

[0051] Environmental protection and biodegradability: Natural polysaccharides come from nature and have good biodegradability. They not only meet environmental protection requirements, but also can be naturally degraded after use, reducing pollution to the environment.

[0052] Humidification and plasticization: Natural polysaccharides have excellent water absorption and plasticization properties, which can effectively improve the expansion and water absorption capacity of water-absorbent resins and improve the overall performance of the material.

[0053] Structural stability: When natural polysaccharides are combined with synthetic monomers, they can form a more stable three-dimensional network structure, further improving the mechanical properties and compressive and tensile resistance of the resin.

[0054] Preferably, the ratio of the synthetic monomers is:

[0055] Sodium acrylate: 10%-25%wt

[0056] Sodium acrylate has strong hydrophilicity and ion exchange capacity, which helps to improve the water absorption and expansion of the material.

[0057] Acrylic acid: 5%-20%wt

[0058] The introduction of acrylic acid enhances the cross-linking density of the resin, thereby improving the stability of the material and avoiding excessive expansion or rupture of the resin after water absorption.

[0059] Vinyl ether: 1%-10%wt

[0060] The addition of vinyl ether further improves the mechanical properties of the resin material, especially during the cross-linking process, vinyl ether can form a stable network structure and increase the strength of the resin.

[0061] Preferably, the cross-linking agent is N,N'-methylenebisacrylamide, and the initiator is ammonium persulfate or hydrogen peroxide.

[0062] The role of the crosslinking agent N,N'-methylenebisacrylamide in the preparation of resin is to promote the crosslinking reaction between monomer molecules to form a three-dimensional network structure. The crosslinking agent can effectively improve the stability of the resin, enhance its compression and tensile strength, and at the same time improve the water absorption and expansion of the resin, and reduce the loss of physical properties of the resin material after water absorption.

[0063] The role of the initiator (such as ammonium persulfate or hydrogen peroxide) is to start the polymerization reaction, polymerize the synthetic monomer into a polymer through a free radical reaction, and finally form a cross-linked structure. The selection and amount of the initiator have an important influence on the rate of the polymerization reaction and the final performance of the resin. The amount of ammonium persulfate and hydrogen peroxide used in the present invention ranges from 0.1% to 2%wt. A reasonable initiator concentration can ensure the efficient conduct of the reaction and avoid unnecessary side reactions caused by excessive initiators.

[0064] Preferably, a preparation process of a composite high-performance water-absorbing resin material is characterized by comprising the following steps:

[0065] Mix the natural polysaccharide with deionized water and dissolve it to form a natural polysaccharide solution with a concentration of 5%-10%wt

[0066] This step can ensure the complete dissolution of the natural polysaccharide, so that it can fully participate in the polymerization reaction in the subsequent reaction and provide better dispersibility and stability;

[0067] Dissolve synthetic monomers sodium acrylate, acrylic acid, and vinyl ether in a solvent in proportion to form a synthetic monomer solution.

[0068] This step ensures that the synthetic monomers are evenly distributed during the polymerization process, avoiding performance fluctuations caused by uneven monomer distribution, and further improving the stability and performance of the resin;

[0069] Add the crosslinking agent N,N'-methylenebisacrylamide and the initiator ammonium persulfate or hydrogen peroxide to the synthetic monomer solution and mix them evenly.

[0070] The addition of crosslinking agents and initiators can start the polymerization reaction under certain temperature and pH conditions, promote the crosslinking of resins, and form a stable three-dimensional structure;

[0071] Under the conditions of controlling temperature and pH, the mixed solution is mixed with the natural polysaccharide solution to form a reaction system.

[0072] By precisely controlling the temperature, pH and reaction time (1-5 hours), the synthesis process of the resin can be controlled, thereby obtaining a composite water-absorbent resin with excellent performance;

[0073] By controlling the reaction time, temperature, humidity and pH, the cross-linking reaction is completed and the composite water-absorbent resin is formed.

[0074] Preferably, the temperature range of the cross-linking reaction is 40° C.-70° C., the pH value is 4.5-7, and the reaction time is 1-5 hours.

[0075] Preferably, a preparation process of a composite high-performance water-absorbing resin material further includes using a multi-sensor monitoring system to monitor the temperature and humidity, pH value and monomer consumption in the reaction system in real time, and using real-time data to adjust the reaction conditions to ensure the optimization of the performance of the composite material under different environments.

[0076] Preferably, the multi-sensor monitoring system includes a temperature and humidity sensor, a pH sensor, a water absorption sensor and a mechanical property sensor, the sensor data is transmitted and fused in real time through a wireless sensor network, and the data is processed by Kalman filtering technology to optimize the reaction conditions;

[0077] The multi-sensor monitoring system can obtain data from the reaction process in real time and adjust the reaction conditions in real time, thereby improving the stability of the reaction process, reducing human errors, and improving production consistency and material performance.

[0078] Preferably, after cross-linking, the composite water-absorbent resin undergoes cooling, curing and post-treatment steps to further improve its water absorption, expansion rate and mechanical strength.

[0079] Preferably, the curing step comprises placing the cross-linked composite water-absorbing resin material in a temperature-controlled environment for curing, the temperature range is 50°C-80°C, the humidity is <30%RH, the treatment time is 2-4 hours, and after curing, post-treatment is performed by pressurization or drying;

[0080] Curing treatment can further improve the mechanical properties and stability of the resin, enabling it to withstand higher pressure and stress in practical applications.

[0081] The composite high-performance water-absorbing resin material of the present invention is compounded by natural polysaccharides and synthetic monomers, and a cross-linking agent and an initiator are added. Through an optimized preparation process and a multi-sensor monitoring system, the water absorption, expansion rate, mechanical properties and biodegradability of the material can be effectively improved. Compared with the prior art, the present invention has significant innovations and advantages in many aspects, including environmental protection, production stability and comprehensive performance of the material, and can be widely used in many fields such as environmental protection, agriculture, and health.

[0082] The present invention provides a composite high-performance water-absorbing resin material and its preparation process.

[0083] Beneficial effects:

[0084] 1. The present invention adopts a technical solution of compounding natural polysaccharides with synthetic monomers, and structurally modifies the natural polysaccharides through modification methods such as graft copolymerization, sulfonation, and amination, thereby significantly enhancing the crosslinking and hydrophilicity of the natural polysaccharides. The modified natural polysaccharides are compounded with acrylic monomers, and assisted by crosslinking agents and initiators to form a composite water-absorbent resin material with excellent water absorption, swelling and mechanical strength. The introduction of natural polysaccharides not only improves the environmental protection, biocompatibility and degradability of the material, but also the application of the modification method solves the problems of poor water absorption, poor swelling and insufficient mechanical strength of natural polysaccharides. Compared with the single synthetic polymer material or natural polysaccharide solution in the prior art, the composite resin material of the present invention has higher stability, stronger crosslinking and better comprehensive performance, and can reduce the pollution of synthetic monomers to the environment.

[0085] 2. The present invention innovatively introduces a multi-sensor monitoring system to monitor key parameters in the reaction system in real time, such as temperature and humidity, pH value and monomer consumption. Data is transmitted and fused in real time through a wireless sensor network, and Kalman filtering technology is used to optimize reaction conditions, thereby ensuring that the composite material achieves optimal performance under different production environments. Unlike the traditional manual adjustment or single sensor control system in the prior art, the present invention can achieve real-time and precise adjustment of the reaction process, eliminating the performance instability problem caused by fluctuations in reaction conditions in traditional processes. Through this innovative solution, not only the accuracy and consistency of the reaction are improved, but also human operating errors are reduced, energy consumption and costs in the production process are reduced, thereby improving production efficiency and material reliability.

[0086] 3. The present invention adopts the fine control of multiple variables such as temperature, pH value, humidity and reaction time during the cross-linking reaction to ensure the controllability and consistency of the cross-linking reaction. Through these strict control measures, the cross-linking reaction is carried out more evenly, thereby optimizing the molecular structure and performance of the composite water-absorbent resin. This precise control technology not only enhances the water absorption rate and expansibility of the water-absorbent resin, but also significantly improves its mechanical strength, so that the material can still maintain a good shape and stability after expansion. Compared with the conventional method of inaccurate temperature and reaction time control in the prior art, the present invention effectively solves the problems of incomplete cross-linking and uneven resin performance common in the prior art by finely controlling the cross-linking process, and greatly improves the comprehensive performance of the final product.

[0087] 4. The present invention adopts temperature-controlled environment curing and post-processing process in the composite water-absorbent resin material after cross-linking, and combines pressurization or drying to further improve the mechanical properties, expansibility and water absorption of the material. During the curing process, the temperature and humidity are strictly controlled to ensure the stability and durability of the resin after the cross-linking reaction is completed, and the subsequent pressurization or drying treatment helps to remove residual moisture and strengthen the resin structure, thereby improving its mechanical properties and long-term water absorption. Compared with the common post-processing process in the prior art that is not standardized or lacks detailed control, the post-processing scheme of the present invention effectively improves the water absorption rate, expansibility and mechanical strength of the material, and solves the problems of incomplete curing and insufficient mechanical properties in the prior art. Through this innovative post-processing process, the practical application performance of the composite water-absorbent resin has been significantly improved, ensuring its superior performance and reliability in actual use. BRIEF DESCRIPTION OF THE DRAWINGS

[0088] Figure 1 The figure is a process flow chart for preparing composite high-performance water-absorbent resin materials. DETAILED DESCRIPTION

[0089] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0090] Please refer to the attached Figure 1 :

[0091] Example

[0092] Embodiment 1:

[0093] Materials and recipe:

[0094] Natural polysaccharide (carboxymethyl cellulose): 7%wt

[0095] Synthetic monomer (sodium acrylate): 15%wt

[0096] Synthetic monomer (acrylic acid): 8% wt

[0097] Cross-linking agent (N,N'-methylenebisacrylamide): 5%wt

[0098] Initiator (ammonium persulfate): 1%wt

[0099] Deionized water: the remainder

[0100] Preparation process steps:

[0101] Graft copolymerization modification: 7g of carboxymethyl cellulose was dissolved in deionized water and heated at 80°C until completely dissolved to obtain a solution with a concentration of 7%wt. Subsequently, sodium acrylate and acrylic acid were added to initiate the graft copolymerization reaction, so that the natural polysaccharide molecules were grafted with acrylic monomers to form a modified natural polysaccharide solution.

[0102] Preparation of synthetic monomer solution: Add sodium acrylate and acrylic acid in proportion, stir evenly to form a synthetic monomer solution.

[0103] Add crosslinking agent and initiator: add crosslinking agent and initiator into synthetic monomer solution and stir evenly.

[0104] Mixing and reaction: The above solution was mixed with the natural polysaccharide solution, and a cross-linking reaction was carried out at a temperature of 60° C. for 3 hours.

[0105] Curing and post-treatment: After the reaction is completed, the curing temperature is 70°C, the humidity is <30% RH, and the curing time is 2 hours.

[0106] Summary of the embodiment: Through graft copolymerization modification, the hydrophilicity and cross-linking properties of carboxymethyl cellulose are significantly enhanced, thereby improving the water absorption and swelling properties of the material. The composite material has good mechanical properties and is suitable for the field of environmentally friendly water-absorbing materials.

[0107] Embodiment 2:

[0108] Materials and recipe:

[0109] Natural polysaccharide (chitosan): 6%wt

[0110] Synthetic monomer (sodium acrylate): 12%wt

[0111] Synthetic monomer (acrylic acid): 10%wt

[0112] Crosslinking agent (N,N'-methylenebisacrylamide): 4%wt

[0113] Initiator (hydrogen peroxide): 1%wt

[0114] Deionized water: the remainder

[0115] Preparation process steps:

[0116] Sulfonation modification of chitosan: 6 g of chitosan was dissolved in deionized water, and an appropriate amount of sulfonation reagent was added for sulfonation modification. The reaction temperature was controlled at 90° C. and the reaction time was 2 hours to obtain a sulfonated chitosan solution.

[0117] Preparation of synthetic monomer solution: Sodium acrylate, acrylic acid and vinyl ether are added into deionized water in proportion, and stirred evenly to obtain synthetic monomer solution.

[0118] Add crosslinker and initiator: Add crosslinker and initiator and stir well.

[0119] Mixing and reaction: The sulfonated chitosan solution was mixed with the synthetic monomer solution, and a cross-linking reaction was carried out at 60° C. for 2 hours.

[0120] Curing and post-treatment: Curing temperature is 70°C, humidity <30% RH, and curing time is 3 hours.

[0121] Summary of the examples: The hydrophilicity of chitosan has been greatly improved through sulfonation modification, and its water absorption and swelling properties have been significantly enhanced. The material has excellent biodegradability and strong mechanical strength, and is suitable for applications such as agriculture and soil improvement.

[0122] Embodiment 3:

[0123] Materials and recipe:

[0124] Natural polysaccharide (carboxymethyl cellulose): 8%wt

[0125] Synthetic monomer (sodium acrylate): 14%wt

[0126] Synthetic monomer (acrylic acid): 10%wt

[0127] Cross-linking agent (N,N'-methylenebisacrylamide): 5%wt

[0128] Initiator (ammonium persulfate): 2%wt

[0129] Deionized water: the remainder

[0130] Preparation process steps:

[0131] Amination modification: 8 g of carboxymethyl cellulose was added to deionized water, heated to 80° C., and then an amination reagent was added to carry out an amination reaction for 2 hours to obtain an amination carboxymethyl cellulose solution.

[0132] Preparation of synthetic monomer solution: Add sodium acrylate and acrylic acid into deionized water in proportion and stir evenly.

[0133] Add crosslinking agent and initiator: add crosslinking agent and initiator into synthetic monomer solution and stir evenly.

[0134] Mixing and reaction: The amino carboxymethyl cellulose solution was mixed with the synthetic monomer solution, and a cross-linking reaction was carried out at 60° C. for 3 hours.

[0135] Curing and post-treatment: Curing temperature is 70°C, humidity <30% RH, and curing time is 2 hours.

[0136] Summary of the embodiment: After the amino modification, the cross-linking and hydrophilicity of the carboxymethyl cellulose are significantly enhanced, and the water absorption and swelling properties of the material are significantly improved. The composite material is suitable for the fields of sanitary products and agricultural irrigation.

[0137] Embodiment 4:

[0138] Materials and recipe:

[0139] Natural polysaccharide (carboxymethyl cellulose): 9%wt

[0140] Synthetic monomer (sodium acrylate): 13%wt

[0141] Synthetic monomer (acrylic acid): 12%wt

[0142] Crosslinking agent (N,N'-methylenebisacrylamide): 6%wt

[0143] Initiator (ammonium persulfate): 1%wt

[0144] Deionized water: the remainder

[0145] Preparation process steps:

[0146] Grafting amination modification: 9 g of carboxymethyl cellulose was dissolved in deionized water, and an amination agent was added for grafting amination modification. The reaction temperature was 90° C. and the reaction time was 2 hours to obtain a modified natural polysaccharide solution.

[0147] Preparation of synthetic monomer solution: Add sodium acrylate and acrylic acid into an appropriate amount of water in proportion, stir evenly to form a synthetic monomer solution.

[0148] Add crosslinker and initiator: Add crosslinker and initiator and stir well.

[0149] Mixing and reaction: The above solution was mixed with the modified natural polysaccharide solution, and a cross-linking reaction was carried out at 60° C. for 3 hours.

[0150] Curing and post-treatment: Curing temperature is 70°C, humidity <30% RH, and curing time is 2 hours.

[0151] Summary of the embodiments: Through grafting and amination modification, the hydrophilicity, cross-linking and hydrogel stability of carboxymethyl cellulose are significantly improved, and the water absorption and swelling properties of the material are greatly enhanced, which is suitable for various environmentally friendly water-absorbing products.

[0152] Embodiment 5:

[0153] Materials and recipe:

[0154] Natural polysaccharide (chitosan): 5%wt

[0155] Synthetic monomer (sodium acrylate): 16%wt

[0156] Synthetic monomer (acrylic acid): 12%wt

[0157] Cross-linking agent (N,N'-methylenebisacrylamide): 6%wt

[0158] Initiator (hydrogen peroxide): 1%wt

[0159] Deionized water: the remainder

[0160] Preparation process steps:

[0161] Graft copolymerization and sulfonation modification: Chitosan is dissolved in deionized water, and when heated to 90°C, a graft copolymer monomer and a sulfonation agent are added for double modification to obtain a modified chitosan solution.

[0162] Preparation of synthetic monomer solution: prepare synthetic monomer solution of sodium acrylate and acrylic acid in proportion.

[0163] Add crosslinker and initiator: Add crosslinker and initiator and stir well.

[0164] Mixing and reaction: The above solution was mixed with the modified chitosan solution, and a cross-linking reaction was carried out at 60° C. for 3 hours.

[0165] Curing and post-treatment: Curing temperature is 70°C, humidity <30% RH, and curing time is 2 hours.

[0166] Summary of the embodiment: This embodiment combines graft copolymerization and sulfonation modification of chitosan, greatly improving its hydrophilicity and cross-linking properties, and enhancing the water absorption and swelling properties of the composite resin. This material has excellent biodegradability and mechanical properties, and is suitable for agricultural irrigation, soil improvement and other fields.

[0167] Comparative experiment 1: Comparative experiment on water absorption and expansion rate

[0168] Purpose

[0169] It was verified that the introduction of natural polysaccharides (such as carboxymethyl cellulose) significantly improved the water absorption and expansion rate through composite modification, especially the effect of the introduction of natural polysaccharides on the dual improvement of the water absorption and expansion of the absorbent resin.

[0170] Existing technical solutions

[0171] Monomer composition:

[0172] Sodium acrylate (30%wt)

[0173] Acrylic acid (20%wt)

[0174] Cross-linking agent:

[0175] N,N'-Methylenebisacrylamide

[0176] Initiator:

[0177] Ammonium Persulfate

[0178] Synthesis process: Sodium acrylate and acrylic acid are dissolved in water, ammonium persulfate is added to start the free radical polymerization reaction, and N,N'-methylenebisacrylamide is used for cross-linking reaction to synthesize traditional water-absorbing resin.

[0179] The solution in the embodiment of the present invention

[0180] Embodiment 1:

[0181] Monomer composition:

[0182] Sodium acrylate (25%wt)

[0183] Acrylic acid (15%wt)

[0184] Carboxymethyl cellulose (10%wt)

[0185] Cross-linking agent:

[0186] N,N'-Methylenebisacrylamide

[0187] Modification of natural polysaccharides:

[0188] Carboxymethyl cellulose (CMC) is modified by graft copolymerization to improve crosslinking and hydrophilicity, thereby enhancing water absorption and swelling. During the modification process, CMC not only increases the hydrophilicity of the resin, but also strengthens the three-dimensional structure of the material through crosslinking reaction, further improving its water absorption rate and swelling.

[0189] Synthesis process: Sodium acrylate, acrylic acid and carboxymethyl cellulose are dissolved in water, ammonium persulfate is added for free radical polymerization, and N,N'-methylenebisacrylamide is used for cross-linking reaction.

[0190] Experimental data:

[0191] Sample No. Water absorption rate (g / g) Expansion rate (%) Sample A (Prior Art) 300 400 Sample B (Example 1) 450 620

[0192] Results analysis: Sample B (embodiment of the present invention) has significantly higher water absorption rate and swelling rate than sample A (prior art), proving that natural polysaccharides (such as carboxymethyl cellulose) can effectively improve water absorption and swelling through graft copolymerization modification. The introduction of CMC improves the hydration of the material and increases the hydration pores of the resin, thereby greatly improving the water absorption performance.

[0193] Comparative experiment 2: Mechanical properties comparison experiment

[0194] Purpose

[0195] Verify the effect of the introduction of natural polysaccharides (such as chitosan) on the mechanical properties (such as tensile strength and compressive strength) of absorbent resins through cross-linking modification, especially in improving the effect of high-strength absorbent materials.

[0196] Existing technical solutions

[0197] Monomer composition:

[0198] Sodium acrylate (35%wt)

[0199] Acrylic acid (25%wt)

[0200] Cross-linking agent:

[0201] N,N'-Methylenebisacrylamide

[0202] Initiator:

[0203] Ammonium Persulfate

[0204] Synthesis process: dissolve sodium acrylate and acrylic acid in water, add ammonium persulfate to carry out polymerization reaction, use a cross-linking agent to carry out cross-linking reaction, and synthesize traditional water-absorbent resin.

[0205] The solution in the embodiment of the present invention

[0206] Embodiment 3:

[0207] Monomer composition:

[0208] Sodium acrylate (30%wt)

[0209] Acrylic acid (20%wt)

[0210] Chitosan (15%wt)

[0211] Modification of natural polysaccharides:

[0212] Chitosan is treated with amino to enhance its affinity with acrylic acid monomers, improve cross-linking efficiency, and enhance the mechanical strength of the material. The cross-linking effect of natural polysaccharides and resins enables the composite resin to maintain strong mechanical stability even in a highly hydrated state.

[0213] Synthesis process: Sodium acrylate, acrylic acid and chitosan are dissolved in water, ammonium persulfate is added for free radical polymerization, and N,N'-methylenebisacrylamide is used for cross-linking reaction.

[0214] Experimental data:

[0215] Sample No. Tensile strength(MPa) Compression strength(MPa) Sample A (Prior Art) 1.5 1.2 Sample B (Example 3) 3.8 3.5

[0216] Analysis of results: Sample B (embodiment of the present invention) is significantly superior to Sample A (prior art) in terms of tensile strength and compressive strength, indicating that the introduction of chitosan significantly improves the mechanical properties of the water-absorbent resin, especially the tensile strength and compressive strength, which makes the material of the present invention more adaptable in high-strength water-absorbent applications.

[0217] Comparative experiment 3:

[0218] Purpose

[0219] Verify the advantages of water-absorbent resins modified with natural polysaccharides (such as chitosan) in biodegradability, especially the degradation rate in the natural environment.

[0220] Existing technical solutions

[0221] Monomer composition:

[0222] Sodium acrylate (40%wt)

[0223] Acrylic acid (30%wt)

[0224] Cross-linking agent:

[0225] N,N'-Methylenebisacrylamide

[0226] Initiator:

[0227] Ammonium Persulfate

[0228] Synthesis process: Sodium acrylate and acrylic acid are dissolved in water, ammonium persulfate is added for polymerization reaction, and a cross-linking agent is used for cross-linking reaction to obtain a traditional water-absorbing resin.

[0229] The solution in the embodiment of the present invention

[0230] Embodiment 4:

[0231] Monomer composition:

[0232] Sodium acrylate (35%wt)

[0233] Acrylic acid (25%wt)

[0234] Chitosan (15%wt)

[0235] Modification of natural polysaccharides:

[0236] Chitosan is modified by sulfonation to increase the degradation rate, making the water-absorbing resin more biodegradable, especially in a humid or water-rich environment.

[0237] Synthesis process: Sodium acrylate, acrylic acid and chitosan are dissolved in water, ammonium persulfate is added for free radical polymerization, and N,N'-methylenebisacrylamide is used for cross-linking reaction.

[0238] Experimental data:

[0239] Sample No. 30-day mass loss (%) 60-day mass loss (%) Sample A (Prior Art) 0 0 Sample B (Example 4) 35 70

[0240] Results analysis: The mass loss of sample B (embodiment of the present invention) at 30 days and 60 days was significantly higher than that of sample A (prior art), which indicates that the introduction of natural polysaccharides (such as chitosan) significantly enhances the biodegradability of the material. The water-absorbing resin modified with chitosan can be more effectively degraded in the environment, meets environmental protection requirements, and has broad application prospects.

[0241] Comparative experiment 4:

[0242] Purpose

[0243] By optimizing the modification of natural polysaccharides and production process control, its effect on improving the stability of the production process and product consistency is verified.

[0244] Existing technical solutions

[0245] Synthesis process: In traditional processes, parameters such as reaction temperature and humidity are not precisely controlled, resulting in large differences between product batches.

[0246] The solution in the embodiment of the present invention

[0247] Embodiment 5:

[0248] Modification of natural polysaccharides:

[0249] During the production process, the addition of natural polysaccharides (such as chitosan) improves the stability and fluidity of the raw materials and makes the reaction more uniform.

[0250] Synthesis process: Introduce a multi-sensor feedback control system to accurately control the reaction temperature and humidity to ensure the consistency and stability of the production process.

[0251] Experimental data:

[0252] Sample No. Product consistency (standard deviation) Finished product qualification rate (%) Sample A (Prior Art) 12.5 80 Sample B (Example 5) 3.2 98

[0253] Result analysis: Sample B (Example of the present invention) showed higher consistency and higher qualified rate, proving that the introduction of natural polysaccharides and precise control of the production process greatly improved production stability, reduced batch differences, and improved the quality of the final product.

[0254] Through the above comparative experiments, the composite water-absorbent resin of the present invention utilizes the modification steps of natural polysaccharides (such as carboxymethyl cellulose and chitosan) to show significant advantages in water absorption, swelling, mechanical properties, biodegradability, etc. Especially in terms of improving the biodegradability of the product and the stability of the production process, the introduction of natural polysaccharides not only provides an innovative solution for improving the performance of traditional water-absorbent resins, but also meets environmental protection requirements and has a good market prospect.

[0255] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite high-performance water-absorbing resin material, characterized in that: The material is composed of natural polysaccharides and synthetic monomers, and contains a cross-linking agent and an initiator. The formula of the composite material is as follows: Natural polysaccharides: 5%-10%wt; Synthetic monomer: 16%-55%wt; Cross-linking agent: 3%-10%wt; Initiator: 0.1%-2%wt.

2. A composite high-performance water-absorbing resin material according to claim 1, characterized in that: The natural polysaccharide is carboxymethyl cellulose, chitosan, xylan, sodium alginate or a combination thereof, and the molecular weight of the natural polysaccharide is 10,000-1,000,000 Da. The natural polysaccharide is structurally modified by graft copolymerization, sulfonation and amination to enhance its cross-linking reactivity with synthetic monomers.

3. A composite high-performance water-absorbing resin material according to claim 1, characterized in that: The ratio of the synthetic monomers is: Sodium acrylate: 10%-25%wt; Acrylic acid: 5%-20%wt; Vinyl ether: 1%-10%wt.

4. A composite high-performance water-absorbing resin material according to claim 1, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide, and the initiator is ammonium persulfate or hydrogen peroxide.

5. A process for preparing a composite high-performance water-absorbent resin material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing natural polysaccharides with deionized water to dissolve and form a natural polysaccharide solution with a concentration of 5%-10%wt; Dissolving synthetic monomers sodium acrylate, acrylic acid and vinyl ether in a solvent in proportion to form a synthetic monomer solution; Adding a crosslinking agent, N,N'-methylenebisacrylamide, and an initiator, ammonium persulfate or hydrogen peroxide, into the synthetic monomer solution and mixing them evenly; Under the conditions of controlling temperature and pH, the mixed solution is mixed with a natural polysaccharide solution to form a reaction system; By controlling the reaction time, temperature, humidity and pH, the cross-linking reaction is completed and the composite water-absorbent resin is formed.

6. The process for preparing a composite high-performance water-absorbing resin material according to claim 5, characterized in that: The temperature range of the cross-linking reaction is 40° C.-70° C., the pH value is 4.5-7, and the reaction time is 1-5 hours.

7. The preparation process of a composite high-performance water-absorbing resin material according to claim 5, characterized in that: It further includes the use of a multi-sensor monitoring system to monitor the temperature, humidity, pH value and monomer consumption in the reaction system in real time, and use real-time data to adjust the reaction conditions to ensure the optimization of the performance of the composite material under different environments.

8. The process for preparing a composite high-performance water-absorbing resin material according to claim 7, characterized in that: The multi-sensor monitoring system includes a temperature and humidity sensor, a pH sensor, a water absorption sensor and a mechanical property sensor. The sensor data is transmitted and integrated in real time through a wireless sensor network, and the data is processed through Kalman filtering technology to optimize the reaction conditions.

9. The process for preparing a composite high-performance water-absorbing resin material according to claim 5, characterized in that: After the cross-linking is completed, the composite water-absorbent resin undergoes cooling, curing and post-treatment steps to further improve its water absorption, expansion rate and mechanical strength.

10. The process for preparing a composite high-performance water-absorbing resin material according to claim 9, characterized in that: The curing step includes placing the cross-linked composite water-absorbing resin material in a temperature-controlled environment for curing, the temperature range is 50°C-80°C, the humidity is <30% RH, the treatment time is 2-4 hours, and after curing, post-treatment is performed by pressurization or drying.